Prevalence and viral load of oncogenic human papillomavirus (HPV) in pterygia in multi‐ethnic patients in the Malay Peninsula. (18th July 2014) - Chong, Pei Pei; Tung, Chee Hong; Rahman, Nurul Asyikin bt Abdul; Yajima, Misako; Chin, Fee Wai; Yeng, Crystale Lim Siew; Go, Eng Soon; Chan, Cordelia M. L.; Yawata, Nobuyo; Yamamoto, Naoki
Abstract Purpose The aim of the study was to determine the prevalence of human papillomavirus (HPV) in primary and recurrent pterygia samples collected from different ethnic groups in the equatorial Malay Peninsula. Methods DNA was extracted from 45 specimens of freshly obtained primary and recurrent pterygia from patients and from 11 normal conjunctival swabs from volunteers with no ocular surface lesion as control. The presence of HPV DNA was detected by nested PCR. PCR‐positive samples were subjected to DNA sequencing to determine the HPV genotypes. Real‐time PCR with HPV16 and HPV18 type‐specific TaqMan probes was employed to determine the viral DNA copy number. Results Of 45 pterygia samples with acceptable DNA quality, 29 (64.4%) were positive for HPV DNA, whereas all the normal conjunctiva swabs were HPV negative. Type 18 was the most prevalent (41.4% of positive samples) genotype followed by type 16 (27.6%). There was one case each of the less common HPV58 and HPV59. Seven of the samples harboured mixed infections of both HPV16 and HPV18. All the four known recurrent pterygia samples were HPV‐positive, whereas the sole early‐stage pterygium sample in the study was HPV‐negative. There was no significant association between HPV‐positive status with gender or age. A high proportion of patients from the Indian ethnic group (five of six) were HPV‐positive, whereas the Malay patients were found to have higher HPV positivity than the Chinese. The viral load of HPV18 samples ranged between 2 × 102 and 3 × 104 copies per μg, whereas the viral load of HPV16 specimen was 4 × 101 to 102 copies per μg. Conclusion This report describes for the first time the quantitative measurement of HPV viral DNA for pterygium samples. The high prevalence of oncogenic HPVs in our samples suggests a possible role for HPV in the pathogenesis of pterygia. Moreover, the relatively low HPV viral load is concordant with the premalignant nature of this ocular condition.